The calculation of parameters and designe of «Plasma focus» facility - Zhukeshov, A. M.; Useinov, B. M.; Gabdullina, A. T.; Amrenova, A. U.; Serik, K. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
In this paper, the plasma focus type devices are seen as an alternative to traditional magnetic systems and laser fusion. The authors present the researches results of plasma formation on the ”CPA-30” plasma accelerator and plasma installation “Focus fusion”...
Keywords: calculation of parameters; magnetic systems; laser fusion; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics